Penggunaan Metode Libqual+Tm untuk Mengukur Kualitas Layanan di UPT Perpustakaan UNP - Aliza, Destia Nur; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This paper discussed about librarians service quality toward users. The librarians of the Library of Padang State University were chosen as an object of a research. Data was collected through questionaires those were given to 40 users who were taken as a sample by using random sampling technique. The data was analized by using the Libqual+TM method. Based on the results of the research, it is concluded that the index score of satisfaction users (IKP) in each dimension of Libqual+TM are: (1) the ability and attitude of librarians in serving (service Affect-sa), in a value of IKP 12%, (2)facilities and atmosphere of the space dimension of the library (library as place-lp), in a value of IKP 13.80%, (3) the instructions and means of access (personal control-pc), in a value of 14.66% IKP, (4) access to information (information access-it) in a value of 13.15% IKP.Keyword: libqual + tm, service.